Public's acceptance of automated vehicles: the role of initial trust and subjective norm. (November 2019) - Zhang, Tingru; Tan, Haibo; Li, Shuling; Zhu, Haoyu; Tao, Da
This study aimed to investigate factors that determine public's acceptance of automated vehicles (AVs) by proposing and empirically testing an AV acceptance model. The model was developed by incorporating two factors, i.e., trust and subjective norm, into the Technology Acceptance Model. The validity of the model was confirmed with a structure equation modeling analysis based on data collected from 395 survey samples. It was found that trust was the most critical determinant of public's acceptance of AVs and offered a way for other factors (i.e. perceived usefulness and social norm) to impact AV acceptance. Subjective norm was also identified as an important factor in shaping users' usage intention, at lease in China, a country dominated by collectivistic culture. Findings from this study provide some guidelines in improving AV products to attract users.